Adobe Animate CC Application As Alternative Learning Media For School Students Elementary School At State Elementary School 01 Bengkulu City - Alparisa, Egen Tri; Wahyudi , Jusuf; Sudarsono , Aji (CV. Generasi Insan Rafflesia, 2022)
This study entitled Adobe Animate CC Application as an Alternative Learning Media for Elementary School Students at Sd Negeri 01 Bengkulu City aims to be used as a tool that can help teachers and students in teaching and learning activities. In this learning media, subject matter is presented at SD Negeri 01 Bengkulu City, especially grade 5. This learning media is built using Adobe Animati CC. Besides presenting the subject matter, there is also a quiz for each lesson as a benchmark for students to understand the lesson. With this learning media application, it is expected that students of SD Negeri 01 Bengkulu City, especially grade 5 students, have an increased interest in learning. Overall the application consists of the school profile menu, subject matter and quizzes, and the application runs well in accordance with the existing menus. Where the profile menu displays a brief profile of SD Negeri 01 Bengkulu City, the Material Menu displays the material studied by students and the Quiz consists of questions in the form of multiple choice..